Macro-Anatomical Investigations on the Skeletons of Porcupine (Hystrix Cristata) II. Ossa Membri Pelvini - Yilmaz, Sadik; Dinç, Gürsel; Aydin, Ali (My University, 1999)
The aim of this study was investigated the bones of pelvic limb of two porcupines (Hystrix cristata). Incisura acetabuli was narrow and when examining at ventral direction the surface areas of the ilium bones were parallel while the wing (ala ossis ilii) and the body (corpus ossis ilii) were very wide and narrow, respectively. The iliac tuberosity (tuberositas iliaca) was approximately 2/3 of the sacropelvic surface (facies sacropelvina). The tuber coxae is beak shaped. The iliac crest (crista iliaca) was convex. Foramen obturatum is very large, tuber ischiadicum with single prominence, and arcus ischiadicus slightly marked. The fovea capitis was absent on the caput ossis femoris and arciform grooves of the cochlea tibiae nearly sagittal. The fibula was proximally located adjacent to the tibia and has distally formed a joint The lateral half of the trochlea tali was bigger than its medial half. A small bone (scaphoide accessoire) was situated to medial aspect of collum tali and dorso-medial aspect of os naviculare. The metatarsal bones were five, in which os metatarsale III was the longest while os metatarsale I was the smallest.
Oklu Kirpi (Hystrix cristata) İskelet Sistemi Üzerinde Makro-Anatomik Araştirmalar II. Ossa Membrini Pelvini
Keywords: Hystrix cristata; Ossa membri pelvini; Porcupine